1982
DOI: 10.1190/1.1441282
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric induced very low‐frequency electric field wavetilt changes

Abstract: Very low‐frequency (VLF) electric field wavetilt measurements were made continuously over a period of four months at a fixed location. Daytime and nighttime values of the wavetilt were found to be relatively constant. During sunrise and sunset the wavetilt decreased to 20 percent of the daytime value, making wavetilt measurements meaningless for two three‐hour intervals during a 24 hour period. A mechanism involving modal interference is postulated.This phenomenon may be a problem in other passive electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Hermance [1982d, 1983a] has used DC thin sheet models to model telluric distortion effects from surface inhomo-geneities. Park et al [1983] and Park [1985] have identified three distortion mechanisms caused by 3D media: coupling between the upper crust and mantle across a resistive lower crust, resistive coupling of conductive features within the upper crust, and local induction of current cells within finite-size, good conductors. The first two of these produce telluric distortion that is frequencyindependent at low frequencies, while the latter is usually frequency-dependent.…”
Section: The Further Development Of 2d and 3d Modelling Codes Must Inmentioning
confidence: 99%
See 4 more Smart Citations
“…Hermance [1982d, 1983a] has used DC thin sheet models to model telluric distortion effects from surface inhomo-geneities. Park et al [1983] and Park [1985] have identified three distortion mechanisms caused by 3D media: coupling between the upper crust and mantle across a resistive lower crust, resistive coupling of conductive features within the upper crust, and local induction of current cells within finite-size, good conductors. The first two of these produce telluric distortion that is frequencyindependent at low frequencies, while the latter is usually frequency-dependent.…”
Section: The Further Development Of 2d and 3d Modelling Codes Must Inmentioning
confidence: 99%
“…A fluxgate instrument would also be easier to deploy in the field. Theoretical analyses that elucidate some important design criteria for sensitive, low noise fluxgates are given by Russell et al [1983] and Narod and Russell [1984]. Three companies are now manufacturing ring-core fluxgates similar to those flown in MAGSAT.…”
mentioning
confidence: 99%
See 3 more Smart Citations